(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
In world literary studies, scientific research is being conducted on the study of the creative works of figures who distinguished themselves with their artistic works, the re-analysis of their unique place in the history of the people and nation, the assessment of the forms of poetic thinking, the works of various genres created by them from an artistic and aesthetic point of view based on the requirements of the new era.